A Rectangle-quartet Metamaterial for Dual-band Perfect Absorption in the Visible Region - Ngoc, Nguyen Van; Hien, Nguyen Thi; Ha, Duong Thi; Tung, Bui Son; Hai, Bui Xuan Son; Lam, Vu Dinh; Xuan Khuyen, Bui (Communications in Physics, 2022)
Based on rectangle-shaped structures, we create a dual-band metamaterial perfect absorber (DMPA) in the optical region. The independent-polarization absorption is a significant advantage as well as the simple integrated progress for constituent materials. In particular, absorption can be obtained to be over 90% in a bandwidth of 140 THz (from 608 THz to 748 THz), which is still remained well in the oblique incident angles for the TE-polarization. Our results can be regarded as the groundwork for the near future applications such as photodetectors, energy converters and more.